A water-soluble nucleolin aptamer-paclitaxel conjugate for tumor-specific targeting in ovarian cancer. Issue 1 (December 2017) - Li, Fangfei; Lu, Jun; Liu, Jin; Liang, Chao; Wang, Maolin; Wang, Luyao; Li, Defang; Yao, Houzong; Zhang, Qiulong; Wen, Jia; Zhang, Zong-Kang; Li, Jie; et al.
Abstract Paclitaxel (PTX) is among the most commonly used first-line drugs for cancer chemotherapy. However, its poor water solubility and indiscriminate distribution in normal tissues remain clinical challenges. Here we design and synthesize a highly water-soluble nucleolin aptamer-paclitaxel conjugate (NucA-PTX) that selectively delivers PTX to the tumor site. By connecting a tumor-targeting nucleolin aptamer (NucA) to the active hydroxyl group at 2′ position of PTX via a cathepsin B sensitive dipeptide bond, NucA-PTX remains stable and inactive in the circulation. NucA facilitates the uptake of the conjugated PTX specifically in tumor cells. Once inside cells, the dipeptide bond linker of NucA-PTX is cleaved by cathepsin B and then the conjugated PTX is released for action. The NucA modification assists the selective accumulation of the conjugated PTX in ovarian tumor tissue rather than normal tissues, and subsequently resulting in notably improved antitumor activity and reduced toxicity. Paclitaxel, a first line chemotherapeutic drug, suffers from poor water solubility and low tissue selectivity. Here, the authors report a water-soluble nucleolin aptamer-paclitaxel conjugate that selectively accumulates in ovarian tumor issues displaying reduced toxicity and improved activity profiles.